EFFECIVITY OF BRAIN GYMNASTIC TO PREVENTION DEMENTIA TO ELDERLY IN THE GLODOGAN SOURTH KLATEN - Paryono .; Isti Khotimah; Witriyani . (STIKES DUTAGAMA KLATEN, 2015)
Background : growing older will increase dementia factor and can decreasing of concentration and remembrance in elderly people. Dementia can restain by brain – gymnastic, it can increase stimulation in brain so they can remember well or have good remembrance. The interview result from some respondence, respondence have trouble such as they usually forget about time where they put their goods. In there village many villager get descent of dementia and increace the number of dementia. Objective : ti find out efectivity of brain – gymnastic to prevention dementia to elderly people in the South Klaten. The Method of research : use quasy eksperiment with pre test and post test design qualitative. Population and sample in this research is 20 respondent, they are 10 treatment responden and 10 control respondent. Sampling by purposive sampling with univariate and bivariate analize. Result : the different result of treatment respondent and control respondent with Mann-Whitney U-Test get significan score 0.103 p> 0.05 and t -1.629. Conlusion : brain – gymnastic is not effective for prevention dementia for elderly in the Glodogan, South Klaten.